(untitled) (Revista de Ensino em Artes, Moda e Design, 2020)
This study presents the result of the application of the methodological phases of the MODThink model by Emídio (2018), in the context of an academic project of the first series of the Fashion Design course at the State University of Londrina. It demons- trates how, through the application of the bionic creativity tool, it was possible to in- clude the concept of the project in product modeling, in addition to contributing to as- pects of production aimed at sustainability. It helps to establish a common language between the design and modeling area, using design tools and creativity techniques as cognitive resources to enhance students’ mental structures in the construction of modeling knowledge.